Intimal hyperplasia after vascular injury is inhibited by antisense cdk 2 kinase oligonucleotides. - Morishita, R (1994)
The cell cycle regulatory enzyme, cdk (cyclin-dependent kinase) 2 kinase, is activated in the rat carotid artery after balloon angioplasty injury, and may mediate smooth muscle proliferation. To test the hypothesis that inhibition of the expression of this key enzyme can inhibit intimal hyperplasia, we studied the effect of antisense phosphorothioate oligodeoxynucleotides (ODN) against cdk 2 kinase administered by intraluminal delivery using hemagglutinating virus of Japan (HVJ)-liposome-mediated transfer. The specificity of antisense cdk 2 ODN was confirmed by the observation that mRNA level of cdk 2 kinase in injured vessels was markedly diminished by the antisense ODN treatment. At 2 wk after transfection, antisense cdk 2 ODN treatment (15 microM) resulted in a significant inhibition (60%) in neointima formation, compared with sense ODN-treated and untreated vessels. Since we have previously observed that cell division cycle 2 kinase mRNA was also activated after vascular injury, we administered the combination of antisense cdc 2 and cdk 2 ODN in this study. Antisense cdc 2 ODN alone (15 microM) only reduced intimal formation by 40%. Combined antisense treatment resulted in near complete inhibition of neointima formation. To understand the mechanism of the sustained effect of a single antisense ODN administration, we examined kinetics of ODN in the vessel wall. Using phosphorothioate FITC-labeled ODN, we transfected carotid artery using the HVJ-liposome method. Fluorescence localized immediately to the medial layer, and persisted up to 2 wk after transfection. These results demonstrate that a single intraluminal administration of antisense ODN directed to cell cycle regulatory genes (e.g., cdk 2 kinase) using the HVJ method can result in a sustained inhibition of neointima formation after balloon angioplasty in rat carotid injury model.